PENERAPAN LMS-GOOGLE CLASSROOM DALAM PEMBELAJARAN DARING SELAMA PANDEMI COVID-19 - Ommi Alfina (Majalah Ilmiah METHODA, 2020)
This research aims to (1) find out the results of the implementation of Learning Management System (LMS)-Google Classroom in the online learning process for Informatics Engineering students, Universitas Potensi Utama during the COVID-19 pandemic; (2) learn about students' responses to online learning using LMS-Google Classroom. This research is based on the transformation of the course process from face-to-face learning to remote learning (PJJ) by relying on technology as a substitute for learning media, known as distance learning and online learning. This research was conducted using case study methods. This research was conducted on informatics engineering students in multimedia courses. Sampling techniques using purposive sampling methods. The results showed that the application of LMS-Google Classroom to online learning for Informatics Engineering students during the COVID-19 pandemic had a positive effect, especially in terms of absorption related to understanding lecture materials. Based on the results of student questionnaire calculations, it was obtained that as many as 23% of students find it difficult to attend lectures using LMS-Google Classroom which is reviewed in terms of technological efficiency and material understanding level. Meanwhile, 77% of students are happy and enthusiastic about gaining a new learning experience after using LMS-Google Classroom to participate in multimedia lectures. It can be concluded that, the implementation of LMS-Google Classroom in online learning during the COVID-19 pandemic is one of the solutions that can be used so that the lecture process can continue. However, it is necessary to provide assistance and control over student activities to keep students motivated in following the lecture process in the context of online learning.